2023
DOI: 10.32598/irj.20.4.825.3
|View full text |Cite
|
Sign up to set email alerts
|

Disability Among Older Adults Residing in Poldasht, Iran in 2018: The Role of Social Aupport as A Protective Factor

Abstract: Objectives: The present study examined the role of social support in protecting against disability among older people residing in Poldasht, West Azerbaijan Province, Iran in 2018. Methods: This cross-sectional study was undertaken on 305 older adults who were selected by random sampling method. The World Health Organization standardized disability scale (WHODASS2) and multidimensional scale of perceived social support (MSPSS) were applied to collect the data. Data analysis was run through a multiple linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Feng et al (2014) demonstrated that an increase in perceived social support could reduce functional disability among individuals aged 75 years and higher [ 22 ]. Furthermore, Ghasemi et al (2022) reported that social support is a protective factor against disability among older adults [ 16 ]. Social support plays a crucial role in boosting an individual’s ability to cope with stress and become more resilient [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Feng et al (2014) demonstrated that an increase in perceived social support could reduce functional disability among individuals aged 75 years and higher [ 22 ]. Furthermore, Ghasemi et al (2022) reported that social support is a protective factor against disability among older adults [ 16 ]. Social support plays a crucial role in boosting an individual’s ability to cope with stress and become more resilient [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social support can have a positive impact on psychological well-being by promoting positive thinking and healthy behaviors during stressful situations [ 42 ]. Perceived social support can enhance an individual’s ability to manage stress and difficult situations, ultimately leading to a better quality of life [ 16 , 43 ]. The buffer-stress hypothesis suggests that social support can protect individuals from stressors by enhancing their coping abilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations